SEMANTIC DEVIATION ON WILLIAM BLAKE’S SELECTED POEMS - Prafitri, Wilma; Suhatmady, Bibit (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2014)
In this study, we analyzed the existence and the contribution of the semantic deviations in the eight selected poems of William Blake. We tried to answer two problems : what were the semantic deviation found on William Blake’s selected poems and how those deviations contributed to the meaning of the poems. Eight poems were selected from the songs of innocence and songs of experience. Furthermore, we used the qualitative content analysis which involved series of activities in analyzing document and described them based on the related theories of research. After analysing the data, we revealed the following findings: (1) the semantic deviation found on William Blake’s selected poems was formed by three tropes. There were semantic oddity, transference of meaning and honest deception. (2) those deviations contributed to help the poet transmit his point of view about social condition, religious value, love and human to human relationship. They were also used to make the poems more aesthetical and dense in meaning.